Quelle couleur pour les frères ? Regards sur l’habit des Mineurs aux xiiie-xive siècles - Véronique Rouchon Mouilleron (Bulletin du Centre d’Études Médiévales d’Auxerre)
It may be surprising to study the colour of the first Minorites clothing, since neither the Franciscan rule nor the hagiographical writings nor any of the first written accounts show any interest in this element of their clothing. If textual sources remain quite silent about it, painted representations on the contrary increased a lot, in terms of quality and quantity, during the century following the foundation of the Order. Therefore the present article is based upon a visual inquiry. Precisely because textual documentation does not deal with colour, it is not to be taken for granted that images have an equal value when we are only provided with implicit definitions in textual discourse. To check whether this method is appropriate or not, we will consider four different and interrelated ways to study the Franciscan dress on its material side, between 1220 and 1320. The analysis begins with the habit worn by Francis himself, which is known through texts, surviving garments and the earliest depictions of it, made between 1228 (in Subiaco) and 1246 (at the Quattro Santi Coronati in Rome). Then, it deals with the terms and expressions used from the second half of the century, through which the habit got an indefinable colour, which should be neither color niger, nor albus, nor even griseus. Thirdly, a serial analysis of the representations of the early tunic, based on about thirty selected items, will provide with a pictorial corpus of this colour, which seems unspecified as much as instable. Those shades of grey or brown or the great variety of other chromatic choices (from black to pink) are precisely set in the places and the contexts of Franciscan paintings. Finally, this problem pertaining to the cloth colour is connected with the stages of the Order’s institutionalization, by paying special attention to its treatment in the usus pauper controversy, between Conventuals and Spirituals.